Faktor-faktor yang berhubungan dengan kelelahan kerja pada pekerja di PT Bank XYZ Kota Jakarta tahun 2024 - Nugroho, Ari Dwi; Irfandi, Ahmad; Nitami, Mayumi; Shorayasari, Susi (Indonesian Journal of Health Science, 2024)
Work-related fatigue is defined as a decrease in efficiency, work quality, and a reduction in the strength or physical endurance needed to continuously carry out work tasks. The research here aims to understand the Factors Related to Work Fatigue in Workers at PT Bank XYZ, Jakarta City in 2024. The type of research here is quantitative using a cross-sectional study design. The sample selection technique was carried out using non-probability sampling (non-random sampling), with a purposive sampling technique, with a research sample of 88 workers. The results of the univariate analysis interpreted the largest proportion as low fatigue (54.5%), age <35 years (54.5%), poor sleep quality (54.5%), non-risk nutritional status (65.9%), and high workload (54.5%). Based on the results of statistical analysis, it is known that variables related to work fatigue are age (p-value = 0.000), sleep quality (p-value = 0.000), workload (p-value = 0.000), while variables that are not related to work fatigue are nutritional status (p-value = 0.951). Therefore, it is recommended that banking companies always implement sports programs to deal with worker work fatigue, monitor worker nutritional status, evaluate and review the workload that must be completed according to the expertise of each worker. Workers also maintain a healthy diet and make the most of their time to sleep. Kelelahan akibat kerja dimaknai sebagai penurunan efisiensi, kualitas kerja, dan pengurangan kekuatan atau ketahanan fisik yang diperlukan guna senantiasa melaksanakan tugas-tugas pekerjaan. Riset disini bertujuan guna memahami Faktor-faktor yang Berhubungan dengan Kelelahan Kerja Pada Pekerja di PT Bank XYZ Kota Jakarta Tahun 2024. Jenis riset disini berupa kuantitatif memakai desain studi cross sectional. Teknik pemilihan sampel dilaksanakan memakai non-probability sampling (non-random sampling), dengan teknik purposive sampling, dengan sampel riset sejumlah 88 pekerja. Hasil analisis univariat menginterpretasikan proporsi terbesar berupa kelelahan rendah (54,5%), usia < 35 tahun (54,5%), kualitas tidur buruk (54,5%), status gizi tidak berisiko (65,9%), dan beban kerja tinggi (54,5%). Berdasar hasil analisis statistik diketahui variabel yang terkait dengan kelelahan kerja berupa usia (p-value = 0,000), kualitas tidur (p-value = 0,000), beban kerja (p-value = 0,000), sedangkan variabel yang tidak berhubungan dengan kelelahan kerja yaitu status gizi (p-value = 0,951). Maka, disarankan agar perusahaan perbankan untuk selalu mengimplementasikan program olahraga guna menangani kelelahan kerja pekerja, pemantauan status gizi pekerja, melakukan pengevaluasian dan peninjauan kembali beban kerja yang harus diselesaikan disesuaikan dengan keahlian masing-masing pekerja. Pekerja juga menjaga pola makan yang sehat dan memanfaatkan waktu untuk tidur dengan sebaik-sebaiknya.